Strategi Komunikasi Pertanian di Masa Pandemi Covid-19 (Studi Kasus pada Pelatihan Hidroponik Tingkat Dasar di CV. Goodplant Indonesia) - Dhini, Inessa Adella Novian; Winarno, Joko; Widiyanto, Widiyanto (Agritechpedia, 2023)
The Covid-19 pandemic has limited physical encounters and necessitated social distancing. This causes CV. Goodplant Indonesia conducts online hydroponic training as an alternative for participants to continue to gain knowledge and skills in hydroponics without having to meet face-to-face. This research aims to analyze communication strategies, supporting and inhibiting elements, and the effectiveness of online hydroponic training during the Covid-19 pandemic. This research uses a qualitative method with a case study approach. Determination of informants was done by purposive sampling. Data validity uses triangulation of sources and techniques. The results stated that the communication strategy carried out by CV. Goodplant Indonesia in hydroponic training during the Covid-19 pandemic is by implementing several stages, namely getting to know the audience through the hydroponic training registration form to find out the background and needs of the trainees, compiling messages based on the needs of the participants, using educational and persuasive methods, and utilizing new media in the form of Zoom Meeting, WhatsApp, and website. The supporting elements of the online hydroponic training CV. Goodplant Indonesia are the suitability of the message to the needs of the participants, the competence of the training mentor, the delivery media, and the openness of the participants. The inhibiting elements consist of technical barriers in the form of signal interference and errors in the application, semantic barriers in the form of unfamiliar scientific terms in hydroponics, and behavioral barriers in the form of limited interaction and the presence of distractions due to other activities during the training. Online hydroponic training by CV. Goodplant Indonesia during the Covid-19 pandemic was effective. This is in terms of cognitive, affective, and conative aspects. However, offline or face-to-face training remains the main preference for participants. Keywords: Communication Strategy, Covid-19 Pandemic, New Media, Online Training, Hydroponics